Fuel management code system against experimental measurements of the CMRR reactor. (August 2019) - Wang, Guanbo; Qian, Dazhi; Ma, Jimin; Li, Rundong; Yuan, Shu; Leng, Jun; Dou, Haifeng; Tang, Bin
Highlights: Our fuel management computation systems use the deterministic and the MC strategy. We proposed a MC-burnup coupling FM strategy called "burnup related nuclides list". CRs critical position, CRs worth curves and flux distribution experiments are introduced. Abstract: The China Mianyang Research Reactor (CMRR), with a thermal power of 20 MW, is an important high performance research reactor operated in China. In this paper, we introduced the fuel management (FM) computation toolbox and confirmatory experiments performed at this reactor. The toolbox system utilizes two roadmaps, the deterministic strategy as the standard method and the Monte Carlo (MC) strategy as the reference way. Interface glue-code packages for both roadmaps are developed to link the existing kernel codes to perform the input-file generation, data manipulation, and output data processing for fuel cycle analysis. In particular, a new MC based coupling strategy is proposed called the "burnup related nuclides list" method which can perform the FM engineering problem with high accuracy and speed. For the aspect of confirmatory experiments, we emphasize on the methods and instruments, including the control rods (CRs) critical position, the CR worth curve, and the thermal neutron flux distribution. We have developed a reactivity meter to perform the CRs worth measurement using the inverse kinetics method, and employed the Dy-Al foils to perform the thermal neutron flux distribution measurements. All three sets of experiments are performed after each refueling. With these data accumulated over years, our FM toolbox system is profoundly validated for various combinations of fuel burnup and core arrangement. It can be concluded that our FM toolbox and strategies, both the deterministic and the MC way, are satisfactory for the FM mission of our reactor.